Combined Use of Bevacizumab + Interferon A-2 α in the Treatement of Patients with Disseminated Kidney Cancer in Comparison with an Active Monitoring Group - K. Sh. Gantsev; A. A. Khmelevskiy (Креативная хирургия и онкология)
Introduction. Despite the fact that the combined use of bevacizumab and interferon α -2A has been studied extensively and proved to be safe, there will always remain a group of patients for whom continuing the long-term drug treatment after a radical surgery would be unfeasible through personal reasons. This paper presents a comparison of the use of bevacizumab in combination with IFN α -2A and active monitoring in patients with metastatic kidney cancer.Materials and methods. This is a retrospective treatment outcome analysis performed on 24 patients following radical surgery. The clear cell RCC was morphologically verified following the nephrectomy in all the cases. The patients’ ages ranged from 62 to 84, averaging at 73 ± 2.2.Results. The outcomes for patients receiving treatment and those being actively monitored were then assessed for the total of 24 people counting both groups. The average length of time without progression amounted to 12.9 months and 9.8 months in the groups A and B, respectively. The median overall survival rate amounted to 22.3 and 18.7 months in the groups A and B, respectively.Discussion. The results demonstrate rather good indicators for the group of patients with metastatic kidney cancer receiving no drug therapy in comparison with the group receiving treatment in accordance with the classic immunotherapy protocol. No significant or fundamental differences have been observed when the groups studied were compared.Conclusion. A competent case-specific approach to treatment strategies for various metastatic kidney cancer patient cohorts is important both for planning satisfactory survival rate indicators and for maintaining the quality of life suited specifically for each patient.